A study on the status of invasive Tilapia species (Coptodon zillii Gervais, 1848 and Oreochromis aureus Steindachner, 1864) in aquatic ecosystems of Khuzestan province, Iran - Hussein Valikhani; Asghar Abdoli; Bahram HassanzadehKiabi; Farshad Nejat; Mohammad Sadeghsaba; Milad Khosravi (علوم محیطی, 2017)
Introduction: Invasive fishes are a major threat to biodiversity of aquatic ecosystems. Tilapia species are invasive due to reproductive, diet and behavioral characteristics and high resistance to environmental conditions, pollution and diseases. So far, two exotic species Coptodon zillii and Oreochromis aureus and also a native species Iranocichla hormuzensis of these species were reported from Iran. In recent years, exotic tilapia species invaded Iran and its neighboring countries inland waters and have had significant ecological and economic impacts. The aim of this study is to do a preliminary survey on the status of exotic tilapia species in Khuzestan province, Iran. Material and methods: The present study was carried out from November 2014 to September 2015 to determine the abundance of tilapia species (C. zillii and O. aureus) in the Shadegan wetland and some local fishery markets in Khuzestan province. In addition to, we evaluated presence or absence of the species in some cyprinid fish farms in the province. Results and discussion: The results showed that the catchment and supply of C. zillii is high and the species is one of the dominated fish in the Shadegan Wetland. In this study, O. aureus was not caught from the Shadegan wetland but observations show that the species is dispersed to other areas, especially in rivers and its abundance is increased. The tilapia species especially C. zillii are pests in some fish farms and the reduction of fish production was noted. The presence of the species in some fish hatcheries is increased the possibility of their transfer to other regions. Conclusions: At the moment, it seems that the best course of action to take action against tilapia is to prevent them from entering to other bodies of water (especially by aquaculture). The continuous studies to determine various aspects of the introductions, potential range prediction, and regular monitoring should be also considered. Overall, a compilation method and also ecologically sustainable water management, reduction of water contaminants and decrease of fishing pressure on native species should be adopted for controlling and reducing of these species.